Comparison of novel active semiconductor pixel detectorwith passive radiation detectors during the NASA Orion Exploration Flight Test 1 (EFT-1). (November 2017) - Gaza, Ramona; Kroupa, Martin; Rios, Ryan; Stoffle, Nicholas; Benton, Eric R.; Semones, Edward J.
Abstract: The first unmanned flight of the Orion Multipurpose Crew Vehicle (MPCV) was successfully completed on December 5, 2014. The total mission duration was 4.5 h, and the EFT-1 trajectory consisted of a high apogee (∼6000 km, 28.6° inclination), high eccentricity orbit through the Van Allen belts. Radiation measurements on Orion included a novel Battery-operated Independent Radiation Detector (BIRD) based on Timepix hybrid pixel technology, luminescence dosimeters (LiF:Mg, Ti, 6 LiF:Mg, Ti, 7 LiF:Mg, Ti, CaF2 :Tm and Al2 O3 :C) and plastic nuclear track detectors (CR-39). This paper will discuss the advantages of the BIRD instrument with respect to analysis of the environment changes along the flight trajectory using the time stamp tracking capability of the pixel detector. In addition, a dosimetry comparison between the active BIRD instrument and the passive radiation area monitor (RAM) detectors in terms of mission absorbed dose. Highlights: NASA EFT-1 radiation belts measurements performed with BIRD instrument. The BIRD instrument is based on a silicon radiation imaging detector. Time-resolved flux data provided insight into dE/dx variations along the trajectory. Other measurements included luminescence dosimeters and nuclear track detectors. Comparison of BIRD data with passive dosimeters show results within ∼10%.